2011
DOI: 10.1021/ja203946g
|View full text |Cite
|
Sign up to set email alerts
|

Diarylethene-Containing Cyclometalated Platinum(II) Complexes: Tunable Photochromism via Metal Coordination and Rational Ligand Design

Abstract: The synthesis, characterization, electrochemistry, photophysics and photochromic behavior of a new class of cyclometalated platinum(II) complexes [Pt(C(∧)N)(O(∧)O)] (1a-5a and 1b-5b), where C(∧)N is a cyclometalating 2-(2'-thienyl)pyridyl (thpy) or 2-(2'-thienothienyl)pyridyl (tthpy) ligand containing the photochromic dithienylethene (DTE) unit and O(∧)O is a β-diketonato ligand of acetylacetonato (acac) or hexafluoroacetylacetonato (hfac), have been reported. The X-ray crystal structures of five of the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
122
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(129 citation statements)
references
References 100 publications
7
122
0
Order By: Relevance
“…Photosensitization of these cyclometalated ligands and the significant red shift of their closed-form absorption in their cyclometalated iridium(III) [44] and platinum(II) [45] complexes have also been demonstrated (Figure 2.16a). The photochromic behaviors and the absorption properties of the closed forms of these cyclometalated complexes were also found to vary with the nature of the ancillary ligands of the complexes (Figure 2.16b) [44c, 45], which has offered an alternative way to fine-tune the photochromism.…”
Section: Photosensitization Of Diarylethene-containing Ligandsmentioning
confidence: 98%
See 1 more Smart Citation
“…Photosensitization of these cyclometalated ligands and the significant red shift of their closed-form absorption in their cyclometalated iridium(III) [44] and platinum(II) [45] complexes have also been demonstrated (Figure 2.16a). The photochromic behaviors and the absorption properties of the closed forms of these cyclometalated complexes were also found to vary with the nature of the ancillary ligands of the complexes (Figure 2.16b) [44c, 45], which has offered an alternative way to fine-tune the photochromism.…”
Section: Photosensitization Of Diarylethene-containing Ligandsmentioning
confidence: 98%
“…Along with the design of the photochromic diimine ligands, various diarylethene-containing cyclometalated 2-thienylpyridine ligands have also been developed [43,44]. Photosensitization of these cyclometalated ligands and the significant red shift of their closed-form absorption in their cyclometalated iridium(III) [44] and platinum(II) [45] complexes have also been demonstrated (Figure 2.16a).…”
Section: Photosensitization Of Diarylethene-containing Ligandsmentioning
confidence: 99%
“…A condensation reaction between 12 and o−phenylenediamine resulted in two photochromic isomers whose retention times were very close to each other on the TLC plate. The 1 H NMR spectrum showed that the photochromic mixture consisted of two isomers of 2-O and a side product (13). Many attempts to separate these isomers using classic flash column chromatography have failed.…”
Section: −25mentioning
confidence: 99%
“…Although lots of DTE-containing, photochromic metallo-complexes have been reported, just a few examples of NLO properties have been measured or calculated in order to explore their potential usage as NLO switches. 28−36 Recently, Yam et al reported the synthesis and characterization of a new class of DTE-containing cyclometalated Pt(II) complexes 37 (Figure 1). Qiu et al studied the strategy for enhancing the second-order NLO properties in these systems by theoretical method.…”
Section: Introductionmentioning
confidence: 99%